Enhanced CO2 Photoreduction by Ni(OH)2‐x/WO3 Nanofibers with Efficient CO2 Activation and Charge Separation. (17th October 2022) - Lin, Yuan; Huang, Guimei; Chen, Lv; Zhang, Jianhua; Liu, Lijun
Abstract: Electrospun WO3 nanofibers show great potential in solar‐powered CO2 reduction, but they still suffer from rapid charge recombination and difficult CO2 activation. Here, WO3 nanofibers are modified by in situ growth of freestanding oxygen‐vacancy Ni(OH)2‐ x nanosheets, and explored their charge separation and CO2 reduction mechanisms by using in situ characterization techniques and density functional theory (DFT) calculations. Some electrons of Ni(OH)2‐ x transferred to WO3 nanofibers upon hybridization owing to their remarkable different work function, which induces a built‐in electric field (BIEF) at interfaces with directions pointing from Ni(OH)2‐ x to WO3 . Driven by the electric field, the photogenerated electrons flow to Ni(OH)2‐ x, while the holes remain at WO3, achieving spatial charge separation. Further, CO2 adsorbed on Ni(OH)2‐ x shows apparent molecular activation, as suggested by its bent and elongated OCO bonds. The Ni(OH)2‐ x /WO3 nanofibers exhibit an enhanced CO production rate with respect to WO3 (54.4 vs 8.1 µmol g −1 h −1 ). The 13 CO2 isotope tracing experiment confirms that the CO product originated from the input CO2 . This work may inspire the development of more advanced photocatalysts for CO2 activation and photoreduction by defect engineering. Abstract : Electrospun WO3 nanofibers are modified with freestanding oxygen‐vacancy Ni(OH)2‐ x nanosheets. The resulting photocatalyst shows enhanced CO2 reduction performance owing to efficient charge separation driven by an interfacial built‐in electric field and effective CO2 activation of defective Ni(OH)2‐ x .